STRONG LEADERSHIP AND POLITICAL WILL IN FRAUD AVOIDANCE - Safril Hidayat (Asia Pacific Fraud Journal, 2017)
Post reformation, Indonesia emerging as a democratic state. On one side, democracy bringing new chapter in political life, but on the other euphoria of democracy excessively rising. Openness brings negative impacts such as fraud in the financial sector, company that carried out by individual or organized group of people. Government of Indonesia established Indonesia’s Financial Services Authority (OJK). Fraud does not only happen in Indonesia. In many parts of the world fraud occurs and involves politics. It can be seen that the actors who commit fraud come from different back ground and social status. Todays, fraud form of action can be diversed and sophisticated as well as development of modern technology, new regulations, and systems. This research uses a qualitative research design. Analyses were performed by literature review. Thus fraud is fraudulent acts, performed in such a way that benefits yourself / group to harm others (individuals, companies or institutions). Encouragement that helped prompt fraud are as follows: pressure (the urge to commit fraud), opportunities (opportunities that enable fraud), and rationalization (perpetrator to justify his actions). Overall encouragement of fraud is known as the fraud triangle.Based on fraud triangle, the simplest way to avoid fraud by high self-consciuosness, strong political will and law enforecement, and leadership and decentralization